2021
DOI: 10.1111/aej.12490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of apical debris extrusion using clockwise and counter‐clockwise single‐file reciprocation of rotary and reciprocating systems

Abstract: The aim was to evaluate apical debris extrusion produced by a single-file system used in counter-clockwise reciprocation and compare it to rotary singlefile systems used in clockwise rotation and clockwise reciprocation. A total of 100 first mandibular molars were divided into five groups (n = 20): (i) WaveOne Gold Glider and Primary instrument in counter-clockwise reciprocation; (ii) One G and One Curve file in clockwise rotation; (iii) One G and One Curve file in clockwise reciprocation; (iv) TruNatomy Glide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…These results have been confirmed previously as the decreased debris extrusion of reciprocating systems was credited to the balanced force and pressure-less mechanics [ 19 , 28 ]. Predin Djuric et al [ 29 ] when comparing apical debris extrusion produced by a single-file system used in counter-clockwise reciprocation, clockwise rotation, and clockwise reciprocation, the lowest mean values were recorded by clockwise reciprocation groups.…”
Section: Discussionmentioning
confidence: 99%
“…These results have been confirmed previously as the decreased debris extrusion of reciprocating systems was credited to the balanced force and pressure-less mechanics [ 19 , 28 ]. Predin Djuric et al [ 29 ] when comparing apical debris extrusion produced by a single-file system used in counter-clockwise reciprocation, clockwise rotation, and clockwise reciprocation, the lowest mean values were recorded by clockwise reciprocation groups.…”
Section: Discussionmentioning
confidence: 99%
“…TruNatomy which is a very popular and novel system has been evaluated in the recent studies regarding the apical debris extrusion (17, 18). Predin Djuric et al.…”
Section: Discussionmentioning
confidence: 99%
“…Predin Djuric et al. compared the apical debris extrusion using clockwise and counter‐clockwise single‐file reciprocation of rotary and reciprocating systems and reported that TRN used with its glide path in clockwise reciprocation motion caused less apical debris extrusion (18). In another study, where the apical debris extrusion of 5 nickel titanium rotary systems (TRN, Reciproc Blue, Hyflex, Hyflex EDM and Protaper Next) was examined in severely curved root canals, it was notified that TRN system caused least debris extrusion (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations